Aplicação da fluidodinâmica computacional (CFD) no estudo do escoamento de ar e deposição de partículas em vias aéreas pulmonares - Augusto, Liliana de Luca Xavier (Universidade Federal de São Carlos, 2014)
The industrialization process and the fast growth of cities lead to an increase of respiratory diseases and, therefore, lead to the beginning of studies involving particle deposition in human lung airways. This work used Computational Fluid Dynamics (CFD) to evaluate the air flow and particle deposition process in three bifurcations of human respiratory system bronchia, considering three ramifications. The model has been validated by the comparison with experimental data available in the literature. It was considered four inlet rates, which correspond to sleep, resting, moderate activity and intense activity breathing conditions of adult male, with particles diameters varying from 1 to 10 μm. It was observed that the air flow is more intense in the inner region of the model, since it was used a parabolic velocity profile at the inlet, and the presence of secondary motion. The particle deposition increased with the intensity of the activity due to higher momentum of the particles, resulting in greater deposition by inertial impaction. Furthermore, CFD techniques were used to compare the particle deposition process during inhalation and further breath holding and exhalation, separately. It was observed a higher number of deposited particles during breath holding when compared with exhalation, justifying the medical recommendations to hold the breath during few seconds after the inhalation of pharmaceutical aerosols. Lastly, the physical mechanisms of gravitational sedimentation, Brownian diffusion and inertial impaction were evaluated and indicated that gravitational sedimentation is more active for bigger particles, while Brownian diffusion has more importance for particles with smaller diameters, and both have more influence in situations involving low speed. Therefore, it can be concluded that CFD is a viable technique and it can be used to represent the physical phenomena of air flow and particle deposition in the portion of respiratory system considered in this work.
Keywords: Engenharia química; Vias respiratórias humanas; Aerossóis - deposição; Fluidodinâmica computacional; Deposição de partículas; Human airways; Particle deposition; Computational fluid dynamics (CFD); ENGENHARIAS::ENGENHARIA QUIMICA